DESCRIPTION OF OSTEOARTHRITIS CASES IN THE ELDERLY AT PERTAMEDIKA UMMI ROSNATI HOSPITAL, BANDA ACEH CITY - Cahyady, Edy; Siswanto, Eko; Rizkidawati, Rizkidawati; Suherman, Nadya Salsabila; Desreza, Nanda (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2024)
Osteoarthritis (OA) is a condition in which the joints experience a decrease in space and the cartilage is damaged, particularly affecting older individuals with a high Body Mass Index (BMI). The combination of a higher BMI and aging can exacerbate joint issues, leading to an increased likelihood of cartilage deterioration. The purpose of this study is to examine the prevalence of knee osteoarthritis at the Internal Medicine Polyclinic of Pertamedika Ummi Rosnati Hospital in Banda Aceh. The research conducted is quantitative in nature, utilizing an observational approach and selecting 80 patients through purposive sampling. The findings revealed that a majority of cases occurred among individuals aged 55 to 65 years. To prevent obesity and protect the joints from harm, individuals are advised to maintain a nutritious diet, engage in regular exercise, and exercise caution during daily activities.